2008
DOI: 10.1111/j.1365-2958.2008.06258.x
|View full text |Cite
|
Sign up to set email alerts
|

EhMLBP is an essential constituent of the Entamoeba histolytica epigenetic machinery and a potential drug target

Abstract: SummaryEhMLBP has been identified as a protein that specifically binds to methylated long interspersed element (LINE) retrotransposons and rDNA in Entamoeba histolytica. EhMLBP is unique to Entamoeba parasites, which makes this protein a possible drug target for treating amebiasis. In the work described here, we evaluated this potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Since it has been reported that UHRF1 is significantly overexpressed in cells that are infected with the parasite Toxoplasma gondii [75], drugs that downregulate UHRF1 expression, could potentially be useful for preventing parasite proliferation and persistence in host cells. In E. histolytica and other Entamoeba spp., EhMLBP is an essential and unique protein, that is involved in the recognition and binding to methylated retroelements [25,76], and does not share any homology with any human proteins [25]. Its promise as a drug target for amoebiasis is supported by the finding that the activity of EhMLBP can be inhibited by the antitumour compound, distamycin A (IC 50 = 13 µM) [77].…”
Section: Targeting the Recognition Of Methylated Dnamentioning
confidence: 93%
See 1 more Smart Citation
“…Since it has been reported that UHRF1 is significantly overexpressed in cells that are infected with the parasite Toxoplasma gondii [75], drugs that downregulate UHRF1 expression, could potentially be useful for preventing parasite proliferation and persistence in host cells. In E. histolytica and other Entamoeba spp., EhMLBP is an essential and unique protein, that is involved in the recognition and binding to methylated retroelements [25,76], and does not share any homology with any human proteins [25]. Its promise as a drug target for amoebiasis is supported by the finding that the activity of EhMLBP can be inhibited by the antitumour compound, distamycin A (IC 50 = 13 µM) [77].…”
Section: Targeting the Recognition Of Methylated Dnamentioning
confidence: 93%
“…Its promise as a drug target for amoebiasis is supported by the finding that the activity of EhMLBP can be inhibited by the antitumour compound, distamycin A (IC 50 = 13 µM) [77]. In addition, EhMLBP activity has been successfully inhibited by bacteriophages that exposed a specific peptide (Pept3) at their surface [76]. Pept3 alone is unable to inhibit the parasite's growth in culture.…”
Section: Targeting the Recognition Of Methylated Dnamentioning
confidence: 97%
“…The pScramblePept3 plasmid that was previously used to express a scramble peptide fused to a NLS sequence in E.histolytica [30] was used as control. The transfection of E. histolytica trophozoites was performed as described in [52].…”
Section: Methodsmentioning
confidence: 99%
“…EhMLBP was induced by heat shock, and its constitutive overexpression protected trophozoites against heat shock (Katz et al 2012 ) . Treatment of E. histolytica with distamycin A, a drug-blocking EhMLBP binding to methylated LINE DNA in vitro, effectively inhibited the growth of the parasite (Lavi et al 2008 ) . In addition, E. histolytica transfectants containing a phage-expressed peptide speci fi cally binding to EhMLBP also impaired the growth of trophozoites (Lavi et al 2008 ) .…”
Section: Entamoeba Histolytica -Methylated Line-binding Proteinmentioning
confidence: 98%
“…Treatment of E. histolytica with distamycin A, a drug-blocking EhMLBP binding to methylated LINE DNA in vitro, effectively inhibited the growth of the parasite (Lavi et al 2008 ) . In addition, E. histolytica transfectants containing a phage-expressed peptide speci fi cally binding to EhMLBP also impaired the growth of trophozoites (Lavi et al 2008 ) . These data support the view that deciphering the unique features of epigenetic regulation may pinpoint novel targets for antiamebic chemotherapy.…”
Section: Entamoeba Histolytica -Methylated Line-binding Proteinmentioning
confidence: 98%